Ultrastable nitrogen-doped carbon encapsulating molybdenum phosphide nanoparticles as highly efficient electrocatalyst for hydrogen generation. Issue 39 (22nd September 2016) - Pu, Zonghua; Amiinu, Ibrahim Saana; Liu, Xiaobo; Wang, Min; Mu, Shichun
Abstract : MoP NPs@NC shows excellent hydrogen evolution reaction catalytic activities and stabilities in a broad pH range. Abstract : There is a crucial demand for cost-effective hydrogen evolution reaction (HER) catalysts towards future renewable energy systems, and the development of such catalysts operating under all pH conditions still remains a challenging task. In this work, a one-step facile approach to synthesizing nitrogen-doped carbon encapsulating molybdenum phosphide nanoparticles (MoP NPs@NC) is introduced by using ammonium molybdate, ammonium dihydrogen phosphate and melamine as precursor. Benefitting from structural advantages, including ultrasmall nanoparticles, large exposed surface area and fast charge transfer, MoP NPs@NC exhibits excellent HER catalytic activities with small overpotentials at all pH values ( j = 10 mA cm −2 at η = 115, 136 and 80 mV in 0.5 M H2 SO4, 1.0 M phosphate buffer solution and 1.0 M KOH, respectively.). Meanwhile, the high catalytic activities of MoP NPs@NC under both neutral and basic conditions have never been achieved before for molybdenum phosphide-based catalysts. Additionally, the encapsulation by N-doped carbon effectively prevents the MoP NPs from corrosion, exhibiting nearly unfading stability after 100 h testing in 0.5 M H2 SO4 . Thus, our work could pave a new avenue for unprecedented design and fabrication of novel low-cost metal phosphide electrocatalysts encapsulated by N-doped carbon.